Nineteenth-century American women write religion: lived theologies and literature - Wearn, Mary McCartin (Ashgate, 2014)
Focusing primarily on non-canonical texts, this collection takes up the diversity of religious discourse in nineteenth-century women's literature and articulates how American women writers adopted the language of religious sentiment for their own cultural, political or spiritual ends. The contributors examine fiction, political and religious writings, memoirs, and poetry to reveal the complexities of lived religion in women's culture-both its repressive and its revolutionary potential --